ANALYSIS OF THE QUALITY OF THE APPLICATION OF SFAS 45 FINANCIAL STATEMENTS IN ST PETER'S CATHOLIC CHURCH PARISH FIELD EAST - Montaris Silaen (JURNAL MANAJEMEN, 2018)
Indonesian Institute of Accountants (IAI) has anticipated the development of type Nonprofit business in Indonesia through the Statement of Financial Accounting Standards (SFAS) 45 2011 regarding the revision of the Reporting and Accountability of Non- Profit Entities. This study was conducted at the Parish of St. Peter Catholic Church East Medan, which is one type of non-profit organizations. The study aims to determine whether the Catholic Church of St. Peter Parish East Medan already applying IAS 45 on the presentation of its financial statements and to determine whether the Catholic Church of St. Peter Parish East Medan quality financial information is qualified in giving an explanation for the users of financial statements.The analytical method used was a descriptive qualitative method. Qualitative method is the method of discussion of issues that are outlining, describe, compare and explain the data. The results of this study the financial manager of the Catholic Church of St. Peter Parish East Medan has applied SFAS 45 in the presentation of its financial statements, has been presenting the financial statements consist of statements Balance Sheet, Profit and Loss statement, cash flow statement In and Out as well as realization of the budget in accordance with the guidelines compiled and identified by the board at the annual plenary meeting. Parish of St. Peter Catholic Church East Medan own activity report quality financial reporting information that qualified in providing an explanation for the users of its financial statements as understandable, relevant, reliability, and can be compared based on SFAS 45 numbers.